EFL PHONOLOGY: A CASE STUDY OF ENGLISH FRICATIVE PRODUCTION BY INDONESIAN LEARNERS/FONOLOGI BAHASA INGGRIS SEBAGAI BAHASA ASING: STUDI KASUS PELAFALAN BUNYI GESER OLEH MAHASISWA INDONESIA - Ni Luh Putu Sri Adnyani (Balai Bahasa Provinsi Bali, 2021)
AbstractThis study reports the difficulties 40 first-year Indonesian college students, majoring in English, had in pronouncing the English fricatives. The aim of this paper is, first, to reveal how these Indonesian EFL learners produced English fricatives, the order of difficulties, and the pronunciation constraints they experienced. The second aim is to identify the possible causes of the pronunciation difficulties. In collecting the data, two types of tasks were administered: a word-list-reading task (Task 1) and a sentence-list-reading task (Task 2). By using Wilcoxon based T-Test, it was revealed that there was a significant difference in the number of errors in Task 1 and Task 2. There was also an increase in errors in Task 2. The results show that the order of difficulties Indonesian learners had in producing fricative sounds (from the most to the least problematic) were: /v/, /ʃ/, /ð/, /θ/, /z/, /ʒ/, /f/, and /s/. It is likely that the influence of the challenging English spelling system played the most important role in the students’ errors. Other factors such as transfer of L1 and the developmental process also contributed to the errors. This research implies that teachers need to apply certain strategies to meet students’ needs. Keywords: English, fricative, Indonesian students, errors AbstrakPenelitian ini melaporkan kesulitan yang dialami mahasiswa tahun pertama Jurusan Pendidikan Bahasa Inggris dalam melafalkan bunyi geser , urutan kesulitan dan kendala dalam pelafalan bunyi tersebut. Tujuan kedua penelitian ini adalah mengidentifikasi kemungkian sebab-sebab dari kesulitan ini. Dua jenis tugas diberikan kepada siswa untuk mengumpulkan data yaitu tugas membaca daftar kata (Tugas 1) dan tugas membaca daftar kalimat (Tugas 2). Berdasarkan hasil Uji T Wilcoxon terungkap bahwa terdapat perbedaan yang signifikan dari segi jumlah kesalahan dalam mengerjakan tugas I dan tugas 2. Juga terdapat peningkatan kesalahan dalam Tugas 2. Hasil-hasil ini memperlihatkan bahwa urutan kesulitan yang dialami mahasiswa Indonesia dalam melafalkan bunyi frikatif ( dari yang paling bermasalah hingga yang kurang bermasalah ) adalah : /v/, /ʃ/, /ð/, /θ/, /z/, /ʒ/, /f/, dan /s/. Ada kecenderungan bahwa sistem ejaan Bahasa Inggris yang rumit sangat besar pengaruhnya terhadap kesalahan-kesalahan yang dibuat oleh mahasiswa. Faktor-faktor lain seperti transfer dari BI dan proses perkembangan juga berkontribusi terhadap kesalahan-kesalahan tersebut. Implikasi penelitian ini adalah dosen atau guru dapat menerapkan strategi-srategi tertentu untuk memenuhi kebutuhan mahasiswa atau siswa. Kata kunci: bahasa Inggris, bunyi geser, mahasiswa Indonesia, kesalahan